A comparative study using the analytical performance of the level of effectiveness of the attack skill of volleyball - Satar, Khalel (Journal of Physical Education, 2012)
The importance of research to identify the level of effectiveness of the performance of the skill of the attack at the difference, so Arti researcher conduct a comparative study of the level of effectiveness of the performance of the skill of the attack of the Arab teams volleyball using the analysis in order to detect the strengths and weaknesses. And through follow-up to the researcher to match the national team found that there is weakness in the skills of offensive and special skill of the attack and the sample of teams participating in the tournament the Arab East (Iraq - Lebanon - Syria - Palestine) and by the results derived researcher found significant differences in the level of effectiveness of the performance of the skill of the attack and for (Iraq - Lebanon - Syria) and the researcher recommended the need to adopt the principle of the need to Calendar objective in each stage of the different training and competition in the process of selection of standardized tests and analysis programs for the offensive skills to follow up the effectiveness of performance skills and address the volatility in the appropriate times.